A giant arteriovenous malformation of the abdominal wall - Figueiredo, Adriana (2024)
INTRODUCTION: Arteriovenous Malformations (AVMs) are high-flow anomalous connections between the arterial and venous systems composed of dysplastic vessels resulting from aberrant angiogenesis. They are congenital and when symptomatic they rarely manifest before adolescence. Depending on the location, size, stage and severity of the symptoms, treatment options vary from conservative management to surgical resection. We report a case of a giant arteriovenous malformation of abdominal wall (tipe IIIb of Yakes Classification) treated with surgical resection after prior attempts of scleroembolization.. CLINICAL CASE: 54-year-old woman with known history of osteoarticular pathology and dyspepsia presented a mass on the left side of the abdominal wall with hard consistency, warm, slightly pulsating and tenderness to touch with several years of evolution. The mass showed infiltration of the internal and external oblique muscles sparing the transverse muscle. Clinically she presented easy fatigue with efforts. Due to the risk of abdominal wall herniation after excision of the AVM, scleroembolization was considered first-line treatment in this case. This strategy resulted in regression of the mass and symptoms improvement. Four years after the last intervention, the patient presented lesion growth, recurrence and worsening of symptoms with severe interference in the quality of life (QoL). After multidisciplinary discussion, she was proposed for complete resection of the AVM. She was first submitted to scleroembolization with Onyx of identified arterial afferents and sclerosis of the lesion nidus with 2% polidocanol. One month after she underwent successfully total resection of the AVM with the collaboration of General Surgery. CONCLUSION: No unified agreement exists on the best treatment of these complex high flow lesions and it is difficult to establish a comprehensive strategy given the pathology’s clinical variability, complex stratification and the risk of relapse. A case-by-case approach is needed in managing these types of lesions.